Northern European Reformations
XVII, 420 p. 16 illus., 14 illus. in color.
Keywords: This book examines the experiences and interconnections of the Reformations, principally in Denmark-Norway and Britain and Ireland (but with an eye to the broader Scandinavian landscape as well), and also discusses instances of similarities between the Reformations in both realms. The volume features a comprehensive introduction, and provides a broad survey of the beginnings and progress of the Catholic and Protestant Reformations in Northern Europe, while also highlighting themes of comparison that are common to all of the bloc under consideration, which will be of interest to Reformation scholars across this geographical region.